MULTILINGUAL EDUCATION POLICY PRACTICES IN AN ISLAMIC BOARDING SCHOOL INDONESIA - Muhammad Abdurrizal; Sumardi Sumardi; Kristian Adi Putra (UICELL, 2021)
This article explores multilingual education policy practices in an Islamic Boarding School context and how they translated multilingual language policy into their class. Researches on multilingual education policies have been widely conducted in public schools in many countries, but in Indonesia, the topic is relatively under-researched. Indonesia has an educational model born from local wisdom and applies multilingualism for student competence, namely Islamic boarding schools. This case exploratory study takes data from 3 teachers from various subjects such as (English, Religion, Biology) at an Islamic boarding school at the same level as senior high school. Thematic analysis is applied to analyze the phenomenon that occurs regarding the multilingual education policy practices. This study reveals that teachers as agents in multilingual education policies run classes based on beliefs and abilities. Data was collected by interviewing teachers as practitioners in implementing multilingual education policies. The implication of this research is to provide a reference for education practitioners in adjusting to the implementation of multilingual education. Keywords: Language Policy, Multilingual Education, Teaching Practices